A meme-based approach for knowledge mining, organization, and presentation of traditional Chinese settlement culture - Simin Yang; Lina Yi; Hui Guan; Yong Li (Heritage Science, 2023)
Abstract Traditional Chinese settlements are successful examples of harmonious coexistence between man and nature. Traditional Chinese settlement culture (TCSC) is the product of its inhabitants' adaptation to the natural and social environment and has national cultural originality and transmission. Core cultural elements of these being chosen to stay can be considered as memes. This study considers traditional Chinese settlement cultural memes (TCSCM) as a special kind of knowledge, and proposes a meme-based approach to mine, organize, and present traditional Chinese settlement cultural knowledge from a knowledge management perspective. This approach is composed of identifying memes, constructing the memes ontology, and the memes knowledge graph, mainly describing and establishing the memes identification index system, the ontology conceptual framework, and knowledge graph construction rules. In addition, the feasibility of the above work is verified by a case study of Jinggang Ancient town in Hunan province. This study provides new practical ideas for the authentic conservation and industrial construction of TCSC.